Corporate Governance: Role of HR. Issue 4 (October 2019) - Anand, Ritu
Abstract: Corporate governance is one of the most important differentiators of business that is distilled from an organisation's culture, its policies and ethics, especially of the people running the business, and the way it deals with various stakeholders. It represents the relationship among stakeholders that is used to determine and control the strategic direction and performance of organisations. This article establishes the role of corporate governance as an enabler and explores the scope—by protecting valuations of a company, determining industrial competitiveness or differentiating a good mergers and acquisitions deal from a bad one—rather than the barrier it has become today. The article emphasises the sustainability and effective implementation of governance practices through self-regulation and voluntary adoption of ethical code of business conduct, which will naturally ensure compliance with every statutory law and guideline. Considering that the workforce today is multigenerational in an age of hyper-globalisation, one of the key tasks is to garner respect, acceptability and adherence to code of conduct by each employee. It further elaborates on the relevant regulatory laws and rules framed by the government, which act as a broader framework for calibrating the company-level ethical compass. The role of human resources (HR) is to embed corporate governance in all aspects of the business. This article dwells on the fact that HR is responsible for not just formulating code of conduct and policies, but also getting them embedded in spirit within the DNA of every employee. It encompasses various organisational and strategic interventions such as employee communication, effective control systems structuring, corporate sustainability, senior management selection, development and succession planning, international presence, diversity and inclusion mindset, setting the culture, promoting a safe workplace, etc. With the Companies Act in 2013 paving the way for a shift in mindset from a regime of control to that of liberalisation and self-regulation—something that the corporates needed to compete globally—HR plays a crucial role of being the enablers of change and not just 'personnel management'.